A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam - Rowley, Jodi J. L.; Dau, Vinh Q.; Hoang, Huy D.; Le, Duong T. T.; Cutajar, Timothy P.; Nguyen, Tao T. (Zootaxa, 2017)
We describe a new, medium-sized Leptolalax species from Vietnam. Leptolalax petrops sp. nov. is distinguished from its congeners by a combination of having a medium-sized body (23.6–27.6 mm in 21 adult males, 30.3–47.0 mm in 17 adult females), immaculate white chest and belly, no distinct black markings on the head, highly tuberculate skin texture, toes lacking webbing and with narrow lateral fringes, and a call consisting of an average of four notes and a dominant frequency of 5.6–6.4 kHz (at 24.5–25.3 °C). Uncorrected sequence divergences between L. petrops sp. nov. and all homologous DNA sequences available for the 16S rRNA gene are >8%.